The Comparative Study of Cortisol Extraction in Cow’s Milk by Different Extract - Suttikrai, Sopita; Jintana, Ratree; Rassamepong, Tiprawee; Anakkul, Nitira (Journal of Mahanakorn Veterinary Medicine, 2023)
Direct measurement of cortisol in milk interfered with milk lipids. Hormone extraction is essential prior before the measure by using the radioimmunoassay technique. This experiment was designed to study the different extracts: Dichloromethane, Diethyl ether, and Petroleum benzene for cortisol extraction in cow’s milk by using different quantities of milk and dilution of the extract. From the results, it was found that the different quantities of milk on radioimmunoassay affect cortisol extraction. The extraction of 500 µl of milk provides a low recovery percentage (% Recovery) in dichloromethane and diethyl ether extract. Also, the quantities of milk per extract affect cortisol extraction. Dichloromethane extract yielded the highest recovery percentage by diluting 1: 24 and 1: 26 in diethyl ether extract. However, petroleum benzene extract for cortisol extraction was disappointing.